ANALYSIS OF HARD SYNTHESIS ALGORITHMS OF SYSTEMS STABILIZATION - Onishchenko , S. M.; Klimenko, E. L. (Problems of Informatization and Management, 2005)
A group of six algorithms for rigid synthesis of stabilization systems is analyzed. The application of the second of them to the synthesis of nonlinear stabilization systems is considered.